Investigating the Effect of Occupational Well-Being on Job Boredom among Iraqi Physical Education Teachers: The Mediating Role of Motivational Beliefs - Hamid Hadi, Mamoon; Nasiri, Mohammad; Hardan Al-Wani, Maher Abdulhamza; Nasr Esfahani, Davood (KMAN Counseling & Psychology Nexus, 2025)
The purpose of this study was to investigate the effect of occupational well-being on job boredom among physical education teachers in Iraq, with the mediating role of motivational beliefs. This research is descriptive-correlational in nature and applied in purpose. The statistical population consisted of all physical education teachers in Iraq, totaling 25,642 individuals. Given the geographical dispersion of physical education teachers across the country, a sample of 384 teachers was selected using a multi-stage cluster sampling method. Data collection tools included the Occupational Well-Being Questionnaire by Salanova et al. (2015), the Job Boredom Questionnaire by Falman et al. (2013), and the Motivational Beliefs Questionnaire by Wang, Khoo, and Su (2010). Face and content validity of the questionnaires were confirmed by the academic supervisor, and their reliability was assessed using Cronbach’s alpha, yielding coefficients of 0.95, 0.92, and 0.91 for occupational well-being, job boredom, and motivational beliefs, respectively. Data were analyzed using correlation coefficients, multiple regression analysis, and structural equation modeling (SEM). All statistical analyses were conducted using PLS and SPSS software. The findings indicated that occupational well-being significantly affects the motivational beliefs of Iraqi physical education teachers, explaining 26.01% of the variance in motivational beliefs. Furthermore, motivational beliefs had a significant negative effect on job boredom, accounting for 18.31% of its variance. Additionally, occupational well-being showed a significant negative impact on job boredom, explaining 12.04% of the variance in job boredom.